2020
DOI: 10.3390/ijerph17113896
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Friendly Biodiesel/Diesel Blends for Improving the Exhaust Emission and Engine Performance to Reduce the Pollutants Emitted from Transportation Fleets

Abstract: Biodiesel derived from biomass is a renewable source of fuel, and global application of biodiesel in the transport sector has rapidly expanded over the last decade. However, effort has been made to overcome its main shortcoming, i.e., efficiency and exhaust emission characteristics (NOx emissions) in unmodified diesel engines. Biodiesel combustion generally results in lower unburned hydrocarbons (HC), carbon monoxide (CO), and particulate matter (PM) in exhaust emissions compared to fossil diesel. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…In conclusion, the performance testing results showed that Jatropha curcas and soybean oil biodiesel have similar potential for energy conversion and generation compared to conventional diesel fuel. The results also indicated that both biodiesels have the potential to reduce emissions and improve air quality, making them suitable as alternative fuels (Sharma et al, 2020). The findings provide valuable information for the development of sustainable and eco-friendly energy solutions based on Jatropha curcas and soybean oil as feedstocks for biodiesel production (Chi et al, 2021).…”
Section: Characterization Results Of Jatropha Curcas and Soybean Oil ...mentioning
confidence: 71%
“…In conclusion, the performance testing results showed that Jatropha curcas and soybean oil biodiesel have similar potential for energy conversion and generation compared to conventional diesel fuel. The results also indicated that both biodiesels have the potential to reduce emissions and improve air quality, making them suitable as alternative fuels (Sharma et al, 2020). The findings provide valuable information for the development of sustainable and eco-friendly energy solutions based on Jatropha curcas and soybean oil as feedstocks for biodiesel production (Chi et al, 2021).…”
Section: Characterization Results Of Jatropha Curcas and Soybean Oil ...mentioning
confidence: 71%
“…As the engine speed increases, the gas flow increases, and then the pressure in the cylinder and the temperature also increases. For these reasons, the oxidation rate of HC should increase at higher speeds, making possible a significant reduction in HC emissions [4], [19].…”
Section: F Hc Emissionsmentioning
confidence: 99%
“…On the other hand, Yesilyurt and Cesur (2020) [9] studied the process of biodiesel production from Styrax officinalis L. oil and found the parameters that affect the biodiesel yield: catalyst concentration, molar ratio of methanol to oil, reaction time and reaction temperature. Using jatropha biodiesel, polanga biodiesel and microalgae biodiesel leads to hydrocarbon, carbon monoxide and smoke emissions reduction [10]. Biodiesel produced from synthetic biology achieves better physiochemical properties and carbon neutral economy [5].…”
Section: Introductionmentioning
confidence: 99%